Low-temperature n-type doping of insulating ultrathin amorphous indium oxide using H plasma-assisted annealing - Seo, Hojun; Lee, Sang Yeon; Lee, Jeongsu; Kim, Sunjin; Sul, Onejae; Seo, Hyungtak; Lee, Seung Beck (Nanotechnology, 2022)
Low-temperature process compatibility is a key factor in successfully constructing additional functional circuits on top of pre-existing circuitry without corrupting characteristics thereof, a technique that typically requires die-to-die (wafer-to-wafer) stacking and interconnecting. And against thermal annealing, which is mandatory and is possible only globally for activating amorphous oxide semiconductors, the selective control of electrical characteristics of the oxide thin-films for integrated circuit applications is challenging. Here, a low-temperature process that enables n-type doping of the designed region of insulating In2O3 thin-film is demonstrated. A short hydrogen plasma treatment followed by low-temperature annealing is used to increase interstitial and substitutional hydrogen associated bond states creating shallow donor levels in the insulating In2O3 surface to transform the thin-film into an n-type semiconductor. As a result, an In2O3 thin-film transistor with a high on/off current ratio (>108), a field-effect mobility of 3.8 cm2 V-1 s-1, and a threshold voltage of ∼3.0 V has been developed. Compared to performing just thermal annealing, the H-plasma assisted annealing process resulted in an n-type In2O3 thin-film transistor showing similar characteristics, while the processing time was reduced by ∼1/3 and the plasma-untreated area still remained insulating. With further development, the hydrogen plasma doping process may make possible a monolithic planar process technology for amorphous oxide semiconductors.
Keywords: Amorphous indium-oxide; Amorphous oxide semiconductors; C. thin film transistor (TFT); In2O3 thin films; Low- temperature process; Low-temperature fabrication; Lows-temperatures; n-Type doping; Thermal-annealing; Ultra-thin; doping; In2O3; low temperature fabrication; oxide semiconductors; thin-film transistor